Effectiveness of the anemia rematri m-health application on knowledge and attitudes toward anemia among adolescent girls: a quasi-experimental study - Greiny Arisani; Seri Wahyuni (International Journal of Public Health Science (IJPHS), 2026)
Adolescent girls are particularly vulnerable to anemia due to inadequate iron intake, increased physiological demands, and menstrual blood loss. Limited knowledge and unfavorable attitudes toward anemia prevention further exacerbate this problem. Mobile health (m-Health) interventions offer a promising approach to delivering health education tailored to adolescents. This study aimed to evaluate the effectiveness of the Anemia Rematri m-Health application in improving knowledge and attitudes regarding anemia among adolescent girls. A quasi-experimental study with a pretest-posttest control group design was conducted among 108 adolescent girls enrolled in private vocational secondary schools in Palangka Raya, Central Kalimantan, Indonesia. Participants were allocated to either an intervention group (n = 54), which received education through the Anemia Rematri application, or a control group (n = 54), which received educational booklets. Knowledge and attitudes toward anemia were assessed before and after the intervention. The findings revealed significant differences between the intervention and control groups in both knowledge (p < 0.001) and attitudes (p < 0.001). The mean increase in knowledge scores was higher in the intervention group (68.67) than in the control group (40.37). Likewise, the intervention group demonstrated a greater improvement in attitude scores (67.35) compared with the control group (41.65). These findings suggest that the Anemia Rematri m-Health application may contribute to improvements in anemia-related knowledge and attitudes among adolescent girls. The application has the potential to become an innovative strategy for strengthening anemia prevention efforts, particularly through integration into the School Health Program (Usaha Kesehatan Sekolah [UKS]), school-based health promotion initiatives, and digital iron supplementation programs.